The Effect of Talent Management Strategies Achievement on Organizational Agility with Governmental Institutions Employees in the Governorate of MA'AN - Tobeery, Dua'a Shaher (European Scientific Journal, ESJ, 2017)
This study aimed at identifying the effect of talent management strategies carrying out, on organizational agility among governmental employees in the governorate of MA'AN. The population of the study consists of employees working at upper and middle management levels in government agencies in the governorate of MA'AN. They were (112) manager. In order to achieve the objectives of the study, a questionnaire has been developed, and distributed over the study's participants. Results revealed the presence of talent management strategies' effect in accordance with its variables on organizational agility. Based upon the results, the study recommends the following: It is necessary for governmental institutions to be concerned with talent management, and activate it due to its effect on enhancing organizational agility, as it is shown in the participants' responses.